Artificial Intelligence and Symbolic Computation 12th International Conference, AISC 2014, Seville, Spain, December 11-13, 2014. Proceedings - Aranda-Corral, Gonzalo A.; Calmet, Jacques; Martín-Mateos, Francisco J. (Lecture Notes in Artificial Intelligence, 2014)
This book constitutes the refereed proceedings of the 12th International Conference on Artificial Intelligence and Symbolic Computation, AISC 2014, held in Seville, Spain, in December 2014. The 15 full papers presented together with 2 invited papers were carefully reviewed and selected from 22 submissions. The goals were on one side to bind mathematical domains such as algebraic topology or algebraic geometry to AI but also to link AI to domains outside pure algorithmic computing. The papers address all current aspects in the area of symbolic computing and AI: basic concepts of computability and new Turing machines; logics including non-classical ones; reasoning; learning; decision support systems; and machine intelligence and epistemology and philosophy of symbolic mathematical computing.